High Gain and High Directive of Antenna Arrays Utilizing Dielectric Layer on Bismuth Titanate Ceramics - Fwen Hoon, Wee; Mohd Fareq, Abd Malek; Farid Ghani; S. Sreekantan; A. U. Al-Amani (Hindawi Publishing Corporation, 2013)
Link to publisher’s homepage at http://www.hindawi.com